The role of NGOs in recognition and sustainable maintenance of customary forests within indigenous communities: The case of Kerinci, Indonesia. (February 2022) - Harada, Kazuhiro; Habib, Muhammad; Sakata, Yumi; Maryudi, Ahmad
Abstract: In 2013, the Constitutional Court of Indonesia ruled that customary forest areas ( hutan adat ) should not be included in state forest areas. This decision permitted customary communities to claim land rights in Indonesian state forests for the first time. This change required formal legal institutions to recognize forests managed by adat rules (customary, informal institutions) by granting property rights. This study considered two villages in Kerinci District to clarify how customary forests were recognized by district and central governments with support from non-governmental organizations (NGOs). The researchers surveyed documents referencing customary forests and interviewed local residents, NGOs, and other government sectors. The World Wildlife Fund and a local NGO helped to protect both the environment and villagers' rights by developing a formal recognition system of customary forests as district-level institutions, as well as by reinforcing village-level institutions. NGOs' critical support of local communities' field activities strengthened the maintenance of customary forests recognized by the district government. The recognition of customary forests in Kerinci (to which NGOs contributed significantly) has become an antecedent to the national-level customary forest scheme. Highlights: The Indonesian state is constitutionally required to recognize customary forest. However, this recognition is proceeding slowly. NGOs play a key role in supporting local communities to gain this recognition. NGOs also play a key role in developing customary rules for managing forests. Different stakeholders' interests need to be satisfied by the recognition of customary forest.